Pengaruh brand image, persepsi harga dan kualitas layanan terhadap minat beli ulang pada Lazada - Arini Nur Safitri (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2020)
This study aims to examine the effect of brand image, perceived price, and service quality on repurchasing interest in lazada. Respondents in this study were Lazada users in the students of the Faculty of Economics, Sarjanawiyata Tamansiswa University in Yogyakarta. The analysis instruments in this study were data quality test, classical assumption, multiple linear regression, t test, F test, and coefficient of determination. This study shows that brand image has a positive and significant influence on repurchase interest, and service quality has a significant positive effect on repurchase interest. Other results from this study indicate that the perception of prices has a negative influence on repurchasing interest.